y = ln ( x 2) = 2 ln ( x) Now, take the derivative. This is the calculus step. y ′ = ( 2 ln ( x)) ′ = 2 ( ln ( x)) ′ = 2 ( 1 x) = 2 x. In the example above, only one rule was needed to fully expand the expression. The next example shows you how to apply

Get detailed step-by-step answers

Figure out mathematic problems

Get math assistance online

Confidentiality

This calculus video tutorial provides a basic introduction into derivatives of logarithmic functions. It explains how to find the derivative of natural loga